Numerical assessment of coanda effect for wind turbine application - Abdul Hamid, Mohd Faisal (2012)
Various methods of flow control for enhanced aerodynamic performance have been developed and applied, such as continuous, synthetic and pulsed jets, compliant surface, vortex-cell and the like, to dramatically alter the behavior of aerodynamic components such as airfoils, wings, and bodies. In an effort to optimize aerodynamic performance of wind turbine, the use of the Coandă effect, by blowing high velocity jet tangential over a highly curved surface (such as a rounded TE) to increase the circulation and lift has gained renewed interest, in particular with the progress of CFD. The present work review the influences, effectiveness and configurations of Coandă-jet fitted aerodynamic surface, in particular S809 airfoil, to improve its lift augmentation and lift over drag ratio, with a view on its incorporation in the design of wind turbine. For this purpose, a simple two-dimensional CFD modeling using k– omega and k – epsilon turbulence models is utilized to reveal the key elements that could exhibit the desired performance criteria for a comprehensive series of configurations. A parametric study indicates that Coandă configured airfoil can only be effective in a certain range of the TE radius, the jet thickness and the momentum jet size; the location of the jet was found to be effective when it is placed close to the TE. The results are compared with existing experimental data for benchmarking. Three-dimensional configurations are synthesized using certain acceptable assumptions. A trade-off study on the S809 Coandă configured airfoil is needed to judge the optimum configuration of Coandă-jet fitted wind turbine design.